Analisis Perbedaan Tingkat Manajemen Laba Dan Profitabilitas Sebelum Dan Sesudah Akuisisi - Yusnita, Irni (CV. ITTC INDONESIA, 2022)
This study aims to determine whether there is a difference between before and after making an acquisition in the 2011-2019 period by analyzing earnings management and profitability four years before and four years after. This study uses secondary data from the Indonesia Stock Exchange (BEI) in the form of financial reports. The method of determining the sample is by purposive sampling, obtained a sample of 8 companies. The analysis technique used in this study was the Wilcoxon signed test because the data after the normality test was not normal. Based on the analysis, it is found that earnings management as measured by discretionary accruals has a significant difference between before and after making an acquisition, and for profitability as measured by return on equity (ROE) there is also a significant difference between before and after making an acquisition. Thus it can be concluded that there are differences in earnings management and profitability between before and after making an acquisition.